Incidence and characteristics of injury in under-19 academy level rugby league match play: A single season prospective cohort study - Tee, J. C.; Till, K.; Jones, B. (Journal of Sports Sciences, 2019)
Academy rugby league competition is an important step along the pathway to professional status, but little is known about injury at this level of the game. The aim of this research was to establish the nature, incidence and burden of injury in English academy rugby league. Using an observational prospective cohort study design, and a time-loss injury definition, the injury outcomes of three professional rugby league academies were recorded during the 2017 season. A total of 87 injuries occurred in 59 matches for an overall injury incidence of 85 (95%CI 67-103) injuries per 1000 hours played. The mean severity of injury was 22 ± 19 days resulting in an overall injury burden of 1898 (95%CI 1813-1983) days lost per 1000 hours. The tackle event was the most common cause of injury (77% of all injuries). Forwards sustained a greater proportion of injuries than backs (forwards 67% vs. backs 33% of injuries). Concussion (13 (6-20) per 1000 hours) and ankle sprains (11 (4-17) per 1000 hours) were the most commonly diagnosed injuries. The shoulder joint was the most commonly injured site (17 (9-25) per 1000 hours). The incidence of injury for academy rugby league is similar to senior professional rugby league.